2001
DOI: 10.1159/000051639
|View full text |Cite
|
Sign up to set email alerts
|

The Heterogeneous Clinical Spectrum of Genital Herpes

Abstract: Background and Objective: Most data of genital herpes have been collected in STD clinics in the USA where unrecognized forms accounted for 80% of HSV-2 infections. Our aim was to study the clinical features in an outpatient clinic of dermatology. Methods: The charts of 170 patients, previously monitored prospectively for a HIV prevalence study, with culture-confirmed genital herpes or herpetic infection with HSV-2 at any other site presenting between 1995 and 1999 were analyzed. Results: 111 (65%) men and 59 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 31 publications
0
26
0
2
Order By: Relevance
“…In contrast to the worldwide trend of younger people being affected with STIs [4, 12, 13, 14], the mean age of patients with syphilis in Switzerland was higher for males and females with 42 and 36 years, respectively. This trend is also seen for gonorrhoea, affecting most often individuals in their fourth decade, and for genital herpes [15]. …”
Section: Epidemiologymentioning
confidence: 97%
“…In contrast to the worldwide trend of younger people being affected with STIs [4, 12, 13, 14], the mean age of patients with syphilis in Switzerland was higher for males and females with 42 and 36 years, respectively. This trend is also seen for gonorrhoea, affecting most often individuals in their fourth decade, and for genital herpes [15]. …”
Section: Epidemiologymentioning
confidence: 97%
“…53 Clinical manifestations are variable, ranging from asymptomatic to mild or severe signs and symptoms with potential complications such as urinary retention, meningitis, and psychological morbidity. 3,37,94,95 Studies reveal that the majority of HSV2 infections are subclinical and unrecognized by those infected. 24,31,57 Classic primary infection is preceded by a prodrome of localized pain, tingling, or burning sensation lasting up to 24 hours.…”
Section: Genital Herpesmentioning
confidence: 99%
“…3,9,10,12 These include psychological stress; fatigue; exposure to heat, cold, or sunlight; menstruation; sexual intercourse; fever; immunosuppression; corticosteroid administration; laser surgery; local tissue trauma; nerve damage; and change in antiviral activity of the saliva. 5,9,[11][12][13]25,26,[35][36][37][38] Demographics HSV1 accounts for the majority of nongenital HSV-induced infections in humans, 39 with 45% to 98% of the world population and 40% to 63% of the people in the United States reportedly HSV1 seropositive. 32,[40][41][42] Worldwide HSV1 prevalence varies with age, race, geographic location, and socioeconomic status; a higher rate of seropositivity has been reported for less industrialized countries.…”
Section: Introductionmentioning
confidence: 99%
“…Genital ulcers due to HSV-2 is often undiagnosed, susceptible to treatment delay, whereas the lesion may progress to extensive ulceration and the deeper tissues within a week, so that an immediate therapy is required to suppress population that can potentially transmit HIV infection through their mucosal lesion. [9] Eichmann and Lautenschlager [10] conducted research on cases of genital ulcers for 4 years, from 170 patients, 86 patients (51%) showed an atypical morphology of the genital lesions. The most common atypical features found in this case is deep and isolated ulcer.…”
Section: Discussionmentioning
confidence: 99%